Intimacy, Passion, dan Commitment pada Pasangan dengan Istri Penderita Kanker Payudara - Swasti, Dian Daru; Yenny, Yenny (Universitas Mercu Buana, 2022)
Every couple hopes to have three components of love by Sternberg (intimacy, passion, commitment). When a wife has breast cancer, it brings them to a new environment in married life. This study uses qualitative methods with interviews and observations. The subjects selected were a married couple whose wife has breast cancer and their wife were 40-60 years old. This study found that all three couples feel breast cancer brings them to a new environment in married life, bringing their relationship closer and caring for them. But in a different way for each couple.